Atypical hemifacial spasm due to vertebral artery dolichoectasia: rare cause of a rarer clinical entity. (10th July 2013) - Mathur, Tarun; Srivastava, Trilochan; Sardana, Vijay; Jain, Rahul
Abstract : A 32-year-old man presented with atypical left hemifacial spasm (HFS) with MRI showing compression of left facial nerve at the root exit zone. HFS rarely presents atypically with onset in orbicularis oris and later spreading upward to involve the orbicularis oculi as was seen in our case. Atypical presentation of hemifacial spasm is rare and vertebral artery dolichoectasia as the underlying aetiology, like in our case is even rarer and has not been described in literature so far.